1983
DOI: 10.1159/000465314
|View full text |Cite
|
Sign up to set email alerts
|

Posttransfusion Hepatitis in Spain. A Prospective Study

Abstract: The incidence of posttransfusion hepatitis was prospectively investigated in 230 cardiac surgery patients. 40 patients (17.4%) developed clinical and/or biological signs of hepatitis. In 10 cases (25%), the illness was due to hepatitis B virus infection. 1 patient (2.5%) had serological evidence of cytomegalovirus infection with clinical signs of hepatitis. In 29 cases (72.5%), the hepatitis was considered to be due to non-A,non-B agent(s). Of the 29 patients in this latter group, 16 have persistent transamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Monophasic hepatitis had a chronicity rate significantly lower than polyphasic (P < 0.05) and plateau hepatitis (P < 0.01). This interesting feature of transaminase elevations has been documented in other studies (5, 16,[25][26][27]. These data, however, do not support the premise that monophasic disease is less likely to pursue a chronic course.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Monophasic hepatitis had a chronicity rate significantly lower than polyphasic (P < 0.05) and plateau hepatitis (P < 0.01). This interesting feature of transaminase elevations has been documented in other studies (5, 16,[25][26][27]. These data, however, do not support the premise that monophasic disease is less likely to pursue a chronic course.…”
Section: Discussionmentioning
confidence: 51%
“…Iwarson et al (28) reported a case of cirrhosis and chronic active hepatitis in a liver biopsy carried out 1 year from the date of diagnosis, and proved evidence for a rapid evolution of liver cirrhosis with this type of hepatitis. Realdi et al (17) biopsied the liver at 17,25,26,36, and 40 months after the onset of the disease in their five cases of cirrhosis secondary to non-A, non-B posttransfusion hepatitis. Berman et al (4) did not report the time at which biopsies were carried out, and Rakela & Redeker (14), who initially could not find cirrhosis of the liver, demonstrated histologic cirrhotic features in a postmortem specimen of a patient who died 42 months after the onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Viral hepatitis commonly occurs in the absence of ser ologic markers for such known hepatotropic agents as hep atitis A virus (HAV), hepatitis B virus (HBV), cytomegalo virus (CMV) and Epstein-Barr virus (EBV) [1][2][3][4]. This entity termed non-A, non-B hepatitis (NANB) accounts for more than 90% of transfusion-associated hepatitis cases worldwide [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic infection by NANB hepatitis virus may cause a variety of hepatic lesions. Chronic active hepatitis with or without cirrhosis is found in about 60% of patients with post-transfusional NANB hepatitis (2)(3)(4)(5)(6)(7)(8), while chronic persistent hepatitis was the lesion more frequently seen in a few patients who developed chronic liver disease following an episode of sporadic NANB acute hepatitis (3,8,9), suggesting that NANB liver disease is more severe when it develops following blood transfusion.…”
mentioning
confidence: 99%